Zambia - Sanches, E. (Africa yearbook: politics, economy and society south of the Sahara in 2020, 2021)
The Patriotic Front (pf) government, headed by President Edgar Lungu, faced a critical year, having to tackle the political and economic impacts of the Covid-19 pandemic. The calendar for the 2021 elections was readjusted so as to meet the constitutional mark of 12 A ugust. Voter registration reached 83% of eligible voters. While voter registration excluded citizens in the diaspora, it extended the right to vote to detainees for the first time. Lungu’s eligibility to run for the elections was a controversial issue. The Constitution of Zambia Amendment Bill No. 1 0 of 2019 failed to pass the second reading in parliament. A series of by-elections were held, resulting in further consolidation of the pf’s power. Freedom of expression and assembly and political opposition activities were restricted. Zambia strengthened bilateral ties with Saudi Arabia, Japan, Malawi, and the UK. China remained one of the country’s major trade partners and an investor in infrastructural projects. With the Covid-19 shock, the economy contracted by 4–5%, accelerating the debt crisis. Zambia became Africa’s first country to default on its debt, in this case Eurobonds worth $ 42.5 m. The imf held virtual meetings with the country and warned of the need to reduce external borrowing and sustain fiscal adjustment in order to improve macroeconomic performance.